2002
DOI: 10.1038/sj.bjp.0704659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic administration of the novel endothelin antagonist J‐104132 on endothelial dysfunction in streptozotocin‐induced diabetic rat

Abstract: 1 The biosynthesis of endothelin-1 is increased in the diabetic state. So this peptide may cause diabetic vascular complications. We tested this possibility by chronically administering J-104132, a potent orally active mixed antagonist of endothelin A and B (ET A /ET B ) receptors to streptozotocin (STZ)-induced diabetic rats and focusing on changes in endothelial function. 2 The acetylcholine (ACh)-induced endothelium-dependent relaxation was impaired in diabetic rats and this impairment was signi®cantly atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 47 publications
9
40
0
Order By: Relevance
“…Blood Glucose and Animal Body Weights As reported previously, 7,11,12) at the time of the experiment all STZ-treated rats exhibited hyperglycemia, their blood glucose concentrations being significantly higher than those of the agematched nondiabetic control rats (Table 1). Moreover, the body weights of the diabetic rats were significantly lower than those of the age-matched control rats at the time of the experiment ( Table 1).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Blood Glucose and Animal Body Weights As reported previously, 7,11,12) at the time of the experiment all STZ-treated rats exhibited hyperglycemia, their blood glucose concentrations being significantly higher than those of the agematched nondiabetic control rats (Table 1). Moreover, the body weights of the diabetic rats were significantly lower than those of the age-matched control rats at the time of the experiment ( Table 1).…”
Section: Resultssupporting
confidence: 76%
“…We previously reported that acetylcholine (ACh)-induced endothelium-dependent relaxation was impaired in the aorta at 10-12 weeks after streptozotocin (STZ) injection (which creates a model of Type 1 diabetes). 7,11,12) Here, to investigate the possible effect of Citrus unshiu MARC extract we started chronic treatment with this extract immediately after the STZ injection, and continued it for 10 weeks.…”
mentioning
confidence: 99%
“…In addition, ET-1 (a vasoconstrictor peptide secreted from endothelial cell) is thought to play a pathological role in a number of vascular diseases (Goto et al, 1996). Interestingly, it was recently reported that ET-1 can activate PI3-K in several cells (Ishibashi et al, 2000;Kawanabe et al, 2003) and that ET-1 activates NAD(P)H oxidase and induces superoxide production in cultured endothelial and smooth muscle cells (Duerrschmidt et al, 2000;Wedgwood et al, NAD(P)H oxidase is increased in STZ-induced diabetic aortae (Kanie and Kamata, 2002) and that this increase is normalized by the endothelin antagonist, J-104132, suggesting that ET-1 is involved in the increased formation of superoxide anions. Furthermore, we found that chronic administration of a relatively low dose of bezafibrate, which was insufficient to alter the levels of plasma lipids (including total cholesterol, LDL cholesterol, high density lipoprotein (HDL) cholesterol, and triglyceride), exerted an improvement effect on the endothelial dysfunction seen in the aorta in rats with established STZ-induced diabetes.…”
Section: Mechanisms Underlying Impaired Endothelial Function In Diabementioning
confidence: 99%
“…A perturbation of the balance between ETA-and ETBreceptor activities may contribute to the pathogenesis of vascular disease (Brunner et al, 2006;Goto et al, 1996;Kanie and Kamata, 2002;Matsumoto et al, 2004c;Miyauchi and Masaki, 1999). Some, but not all, experimental models of hypertension, atherosclerosis, and diabetes display high levels of circulating ET-1, and exhibit endothelial dysfunction (Barton et al, 1998;Brunner et al, 2006;Kanie et al, 2003;Makino and Kamata, 1998).…”
Section: Pparγ Agonists and The Endothelin Systemmentioning
confidence: 99%
“…Moreover, we recently studied the relationship among the ET-1 system, endothelium-dependent relaxation, and chronic pioglitazone treatment using aortas from STZ-induced diabetic rats (Matsumoto et al, 2007d). In such animals, we previously reported that: (1) the plasma ET-1 level is increased and that this increase may be due to an overexpression of the mRNA for prepro-ET-1 (Makino and Kamata, 1998;Makino et al, 2001), (2) the overproduction of ET-1 seen in STZ-induced diabetes results from the hyperglycemia, not from any increase in either LDL cholesterol or triglyceride (Makino and Kamata, 2000), (3) the expression of the mRNA for p22phox is increased in STZinduced diabetes, an increase that is completely preventable by the chronic administration of J-104132 (a potent, orally active, mixed antagonist of ETA and ETB receptors) (Kanie and Kamata, 2002), and (4) short-term or prolonged treatment with ET-1 impairs endothelial function in the aorta both in nondiabetic rats Matsumoto et al, 2007d) and in rats with established STZ-induced diabetes . Moreover, we have demonstrated that chronic administration of the PPARα agonist bezafibrate to established STZ-induced diabetic rats normalizes both the mRNA for prepro-ET-1 and the plasma concentration of ET-1, while improving endothelium-dependent relaxation (Kanie et al, 2003).…”
Section: Pparγ Agonists and The Endothelin Systemmentioning
confidence: 99%